Late Nineteenth-Century Radical Utopias in Theatre Reviews: Stagings and Reception of Anne Charlotte Leffler’s Sanna kvinnor - Lindh Estelle, Birgitta (Nordic Theatre Studies, 2023)
Anne Charlotte Leffler’s Sanna Kvinnor (True Women 1883) is one of many gender-critical plays by Swedish women playwrights during the 1880s which linger in the shadows of Henrik Ibsen’s A Doll’s House. Sanna kvinnor certainly asks for a change of the prevailing gender norms in the 1880s, in other words, for a transformation into a better world, but how was this utopian drive staged at the theatres and how was it received by the theatre critics? By taking the theoretical point of departure in Slavoj Žižek’s notion of a radical utopia (2003), the aim of my article is to illuminate the reviewers’ perception of the stagings in the first production at the Royal Dramatic Theatre in 1883 and in Albert Ranft’s touring production 1884–86. My archival sources mainly consist of reviews from which both the stagings and the reviewers’ reactions will be traced through a systematic method developed from the semiotics of Jurij Lotman.